ANALISIS ANTESEDEN DAN KONSEKUENSI DARI RELATIONSHIP QUALITY - Salman Faris Insani (STIE Atma Bhakti, 2016)
The paper investigates dan analyzes the factors that become antecedents of Relationship Quality: Client Knowledge, Customer Orientation, Expertise, Similarity, and Communication, and the consequences of the implementation of marketing strategies based on Relationship Quality, consisting of the formation and development of customer’s Purchase Intention and positive Word Of Mouth for the company. The sample in this study is the customer who have used the product of Telkomsel for 2 years or more, been visiting to the office of Grapari Solo, and been interact directly with the customer services. The respondents of this study totaled 179 respondents. The sampling method used was non probability sampling where as the technique used is purposive sampling. By using the Structural Equation Modeling (SEM) analysis, the findings indicate that: Client knowledge is positively related to Relationship Quality; 2) Customer Orientation is positively related to Relationship Quality; 3) Expertise is positively related to Relationship Quality; 4) Similarity have no effect on Relationship Quality; 5) Communication is positively related to Relationship Quality; 6) Relationship Quality is positively related to Purchase Intention; 7) Relationship Quality is positively related to Word Of Mouth. Keywords: Relationship Quality, Purchase Intention, Word Of Mouth.